Physical activity and health-promoting lifestyle of student nurses in Malaysia - Soh, Kim Geok; Yusof, Aminuddin; Soh, Kim Lam; Japar, Salimah; Ong, Swee Leong; Fauzee, Mohd. Sofian Omar (Scientific Research Publishing, 2015)
Studies have indicated that lack of regular physical exercise and not adhering to a health-promoting lifestyle among student nurses are barriers to their encouraging patients to exercise. On the other hand, nurses who personally embrace physical activity are more likely to encourage their patients to improve their health through physical activity or diet. As a result, promoting an active and healthy lifestyle among student nurses is important because this has a crucial role in their subsequently encouraging healthy lifestyles among their patients. The aims of this study were to determine the physical activity levels and health-promoting lifestyles among student nurses in Malaysia, and to investigate whether there was a correlation between the physical activity levels of student nurses and their lifestyle habits. Further investigation was also carried out to correlate lifestyle habits with physical activity during weekdays and at the weekends. This study involved 189 student nurses who were pursuing Diplomas and Bachelor Degrees in local government universities. The Yamax Digi-Walker pedometer was used to measure physical activity, while the Health-Promoting Lifestyle Profile (HPLP) II questionnaire was used to assess the health-promoting lifestyles of the participants. The HPLP II consisted of six sub-scales which included health responsibility, physical activity, nutrition, spiritual growth, interpersonal relations, and stress management. According to the results on physical activity, the student nurses had a mean of 8275.97 ± 2210.174 steps per day and were thus categorised as somewhat active. Additionally, the student nurses were found to be more active during weekends (M = 8389.75, SD = 2689.12) as compared to weekdays (M = 8230.46, SD = 2353.97). According to previous studies, both step counts are classified in the “somewhat active” category. Overall, the results for HPLP II showed that student nurses students in Malaysia had a positive health-promoting lifestyle with a score of 2.58 ± 0.34 on a 4-point Likert scale. The highest score was reported in spiritual growth, with a score of 2.92 ± 0.43. Meanwhile, physical activity was observed to be the lowest, with a score of 1.74 ± 0.39. The results found no correlation between physical activity and overall health-promoting lifestyle among student nurses in Malaysia (r = 0.06, n = 189, p < 0.37). However, there was a significant relationship between physical activity (measured by the pedometer) and physical activity habit (measured through the questionnaire) among the student nurses (r = 0.24, n = 189, p < 0.01). According to the findings, when the participants indicated in the questionnaire that they were active physically, the pedometer readings also showed a corresponding similarity in terms of their daily physical activities.